Animals as domesticates : a world view through history - Clutton-Brock, Juliet (Animal turn., 2012)
"Drawing on the latest research in archaeozoology, archaeology, and molecular biology, Animals as Domesticates traces the history of the domestication of animals around the world. From the llamas of South America and the turkeys of North America, to the cattle of India and the Australian dingo, this fascinating book explores the history of the complex relationships between humans and their domestic animals. With expert insight into the biological and cultural processes of domestication, Clutton-Brock suggests how the human instinct for nurturing may have transformed relationships between predator and prey, and she explains how animals have become companions, livestock, and laborers. The changing face of domestication is traced from the spread of the earliest livestock around the Neolithic Old World through ancient Egypt, the Greek and Roman empires, South East Asia, and up to the modern industrial age."--Jacket.